The Effect of Yttrium Oxide Reinforcement on the Microstructural and Mechanical Properties of Biologically Derived Hydroxyapatite - Bozkurt, Y.; Gokce, H.; Pazarlioglu, S.; Salman, S. (Institute of Physics, Polish Academy of Sciences, 2015)
In the present study, hydroxyapatite used as a matrix material was derived from the femur bones of Meleagris gallapova (MGHA) and then reinforced by yttriyum oxide (Y2O3, 5 and 10 wt%) and then pelleted samples at 350 MPa were sintered between 900 and 1300 °C. Finally, the effect of Y2O3 reinforcement on the microstructural and mechanical properties of MGHA was investigated. Scanning electron microscope (SEM) and X-ray diffraction (XRD) patterns were used to microstructural examinations. Density, microhardness and compressive strengths of composites were used to analyze of mechanical properties of their. Experimental results show that mechanical properties of composites enhance by increasing the temperature. The optimum results were obtained for MGHA-%10 Y2O3 composites sintered at 1200 °C. 2